Hen egg yolk and skinned krill as possible foods for rearing leptocephalus larvae of Anguilla japonica Temminck & Schlegel. Issue 10 (16th April 2012) - Okamura, Akihiro; Yamada, Yoshiaki; Horie, Noriyuki; Mikawa, Naomi; Tanaka, Satoru; Kobayashi, Hideki; Tsukamoto, Katsumi
Abstract: Usual diets for rearing leptocephalus larvae of Japanese eel A nguilla japonica include eggs of the endangered spiny dogfish S qualus acanthias (SE). We investigated the effects of alternative food materials, hen egg yolk (HEY) and exoskeleton‐free (skinned) Antarctic krill (SAK), on the growth and survival of eel larvae. We found that feed comprising whole krill including exoskeleton (WAK) containing higher levels of fluoride (37.89 mg kg −1 ) was acutely toxic to eel larvae exposed to this alone. In contrast, extract from SAK containing lower concentrations of fluoride (4.25 mg kg −1 ) showed no apparent adverse effects. Growth of larvae fed a mixture of SE and SAK in a feed trial of 58 days [mean body weight (BW), 6.0 mg] was about twofold higher than that of larvae fed a mixture of SE and WAK (3.2 mg) ( P  < 0.01). A mixture of HEY and SAK also had some dietary benefits for eel larvae, enabling them to survive for up to 58 days and to grow significantly (mean BW, 2.4 mg), compared with their initial weight (mean BW, 0.2 mg) ( P  < 0.001). Although additional nutritional improvements are needed, the present results suggest that combination diet HEY and SAK may be a good alternative to SE as an effective diet for eel larvae.